Pengaruh Tax Avoidance dan Board Diversity terhadap Kinerja Perusahaan dalam Perspektif Corporate Governance - Ely Kartikaningdyah; Resty Natalia Putri (Pusat P2M Politeknik Negeri Batam, 2017)
The purpose of this research is to analyze the impact of tax avoidance and board diversity on corporate performance in the perspective of corporate governance. The research was conducted for non-financial firms listed on the Indonesia Stock Exchange period 2010 to 2013.In this research, tax avoidance is measured by Cash Effective Tax Rate (CETR), board diversity is measured by 3 proxies, i.e. age, educational background and tenure of the board of directors, and the performance of the company is measured by the Tobin’s Q ratio. Analysis of panel data with fixed effects model was used to analyze the influence of independent variables and the dependent variable. The results of this study indicate that the tax avoidance negatively affects the corporate performance and board diversity not affects the corporate performance.